Assessment of a handheld fluorescence imaging device as an aid for detection of food residues on processing surfaces. (January 2016) - Everard, Colm D.; Kim, Moon S.; Lee, Hoyoung
Abstract: Contamination of food with pathogenic bacteria can lead to foodborne illnesses. Food processing surfaces can serve as a medium for cross-contamination if sanitization procedures are inadequate. Ensuring that food processing surfaces are correctly cleaned and sanitized is important in the food industry to reduce risks of foodborne illnesses and their related costs. A handheld fluorescence imaging device was assessed for detection of three types of food residues that have been associated with foodborne illness outbreaks, i.e. spinach leaf, milk, and bovine red meat, on two commonly used processing surfaces, i.e. high-density polyethylene and food grade stainless steel. Fluorescence excitation at 405 nm was supplied by 4 × 10 W light emitting diodes. Interchangeable optical filters were selected to optimise the contrast between the food residues and processing surfaces, using hyperspectral fluorescence imaging. The fluorescence imaging plus image analysis differentiated food residues from the processing surfaces more clearly than visual inspection in ambient lighting. This optical sensing device can be used to detect food fouling on food processing surfaces over relatively large areas, and has potential for use in the food industry as an aid for detection of specific food residues. Highlights: In-house engineered handheld fluorescence imaging device assessed. Food residues on HDPE and SS food processing surfaces were imaged. Fluorescence excitation supplied by 4 × 10 W light emitting diodes at 405 nm. Interchangeable optical filters were selected to optimise residue-surface contrast. Food residues detected using handheld fluorescence imaging device.